Documents Organisation Strategies of Open University Malaysia (OUM) Postgraduate Students - Kaur, Jaspal; Fathin Fakhriah (2018)
This study aims to investigate student document organisation strategies in their desktops primarily. The most common document management system used by students on their desktops is the hierarchical folder system integrated within their computer operating system.